Necessary optimality conditions for interval optimization problems with inequality constraints using constrained interval arithmetic - Maqui-Huamán, Gino G. [UNESP] (2018)
This article is devoted to obtaining necessary optimality conditions for optimization problems with interval-valued objective and interval inequality constraints. These objective and constraint functions are obtained from continuous functions by using constrained interval arithmetic. We give a concept of derivative for this class of interval-valued functions and we find necessary conditions based on Karush-Kunh-Tucker theorem in their interval version. We present an example to illustrate our results.